Draft Annual Plan 1982-83 Vol. I Union Territory of Chandigarh - Planning Commission (Planning Commission, 1982)
to meet the secure problem of water scarcity in Chandigarh a scheme to tap surface water by drawing water from the Bhakra Mein line has been formulated Rs. 418.29 lakhs has been proposed during the Annual Plan 1982—83. This induces total provision of Rs. 1.00 crores to take up second phase of the Project. The water project will be financed partly by getting loan to the extent of Rs. 3.17 crores from the LIC during the Sixth plan expired.
Planning & Statistical Cell, Finance Department